Could the perception of effort help us unravel the potential of "living low-training high"? A perspective article - Burtscher, M.; Álvarez-Herms, J.; Burtscher, J.; Strasser, B.; Kopp, M.; Pageaux, B. (Journal of Sports Sciences, 2025)
Living low-training high may promote favourable physiological adaptations and improvement of exercise performance in normoxia following training at altitudes above 1500 m. Whether and how physiological adaptations to training high interact with the perception of effort remains unknown. This perspective article aims to carve out potential contributory effects of the perception of effort on performance changes following living low-training high interventions. It is based on two unique case reports, findings on known physiological adaptations to living low-training high, and integration of current knowledge on the neurophysiology of effort perception. Considering the current state of knowledge on the effect of exercising in hypoxia on perceived effort, we propose that the hypoxia exposure associated with living low-training high protocols interact with the perception of effort and its rating, by inducing adaptations that i) slow the development of neuromuscular fatigue and associated compensatory increase in motor command, ii) alter the functioning of the anterior cingulate cortex and/or the motor areas, and iii) alter the interaction with other psychological responses to the exercise. In the proposed framework using a psychophysiological approach, changes in the participants` report of their perceived effort would reflect underlying neurophysiological and psychological adaptations to hypoxia exposure.